Implementasi Teknologi Briket Berbasis Propagul Mangrove sebagai Energi Terbarukan bagi Masyarakat Pesisir Lampulo, Banda Aceh - Irma Dewiyanti; C Yulvizar; R Moulana; N Nurfadillah; C Octavina; M Ulfah; I I Arisa; M S Mubarrak; M Siregar; A Musavi; S Darma; Fikri Fikri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
Mangrove Park Lampulo (MPL) Banda Aceh is a conservation area managed by Pemuda Peduli Mangrove Kutaraja (PEMANGKU), a community group. One of the main issues in this area is the large number of mangrove propagules that fall to the ground or die during the nursery stage, resulting in underutilized materials that accumulate as waste and interfere with the environment and the natural regeneration process of mangroves. On the other hand, coastal communities need environmentally friendly alternative energy sources. This community service activity aims to transfer knowledge and technology on the utilization of mangrove propagule waste as raw material for producing environmentally friendly biofuel briquettes. The methods employed include socialization, education on the potential use of propagules, the development of instruments such as a charcoal kiln, grinding tools, and briquette molding equipment, as well as training and mentoring. The results indicate an increase in knowledge and skills in managing propagule waste into charcoal briquettes. The production process involves collection, cleaning, sun drying, carbonization using a charcoal furnace, grinding the charcoal, mixing with a binder, molding, and drying for 2–3 days. The resulting briquettes have a dense texture, ignite easily, and produce stable heat. The efficiency of converting propagules into briquettes reaches 30–35%, and 5 kg of dried propagules yields approximately 4.8 kg of briquettes. This activity has the potential to support mangrove conservation, improve the local economy through briquette production, and enhance the added value of the conservation area for visitors.